Balancing selection maintains ancient polymorphisms at conserved enhancers for the olfactory receptor genes of a Chinese marine fish. Issue 16 (27th June 2021) - Liu, Qiaohong; Mishra, Mrinal; Saxena, Ayush S.; Wu, Haohao; Qiu, Ying; Zhang, Xinhui; You, Xinxin; Ding, Shaoxiong; Miyamoto, Michael M.
Abstract: The study of balancing selection, as a selective force maintaining adaptive genetic variation in gene pools longer than expected by drift, is currently experiencing renewed interest due to the increased availability of new data, methods of analysis, and case studies. In this investigation, evidence of balancing selection operating on conserved enhancers of the olfactory receptor (OR) genes is presented for the Chinese sleeper ( Bostrychus sinensis ), a coastal marine fish that is emerging as a model species for evolutionary studies in the Northwest Pacific marginal seas. Coupled with tests for Gene Ontology enrichment and transcription factor binding, population genomic data allow for the identification of an OR cluster in the sleeper with a downstream flanking region containing three enhancers that are conserved with human and other fish species. Phylogenetic and population genetic analyses indicate that the enhancers are under balancing selection as evidenced by their translineage polymorphisms, excess common alleles, and increased within‐group diversities. Age comparisons between the translineage polymorphisms and most recent common ancestors of neutral genealogies substantiate that the former are old, and thus, due to ancient balancing selection. The survival and reproduction of vertebrates depend on their sense of smell, and thereby, on their ORs. In addition to locus duplication and allelic variation of structural genes, this study highlights a third mechanism by which receptor diversity can be achieved for detecting and responding to the huge variety of environmental odorants (i.e., by balancing selection acting on OR gene expression through their enhancer variability).